Reading Beyond the Book with Primary Sources. (12th April 2022) - Rodríguez, Noreen Naseem; Falkner, Anna; Bohl, Elizabeth Tetu
Abstract: In a time when some nonfiction historical books for children and young adults have drawn concern and critique for sharing difficult histories, teachers may be looking for ways to contextualize those narratives and provide more support for students as they engage in these histories. Going beyond the book with primary sources can help provide that context, and can create opportunities for critical reflection, historical thinking, and analysis.